2017
DOI: 10.1186/s11671-017-2174-x
|View full text |Cite
|
Sign up to set email alerts
|

A New Method Without Organic Solvent to Targeted Nanodrug for Enhanced Anticancer Efficacy

Abstract: Since the hydrophobic group is always essential to the synthesis of the drug-loaded nanoparticles, a majority of the methods rely heavily on organic solvent, which may not be completely removed and might be a potential threat to the patients. In this study, we completely “green” synthesized 10-hydroxycamptothecine (HCPT) loaded, folate (FA)-modified nanoneedles (HFNDs) for highly efficient cancer therapy with high drug loading, targeting property, and imaging capability. It should be noted that no organic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 200 FA-modified chitosan nanoneedles ( Figure 5 ) and micelles exhibit significantly enhanced cellular uptake, higher cytotoxicity against folate-receptor-positive tumor cells. 201 , 202 Loaded with HCPT and MTX-dual drug chitosan NPs that exhibit sustained and prolonged drug release properties, as well as effective cellular internalization and enhanced cytotoxicity. 203 Studies have shown that nitric oxide (NO) is an endogenous gas transmitter can overcome multidrug resistance (MDR) by making nitrification of certain tyrosine residue of P-glycoprotein (Pgp) to inhibit the pumping function.…”
Section: Organic Npsmentioning
confidence: 99%
See 1 more Smart Citation
“… 200 FA-modified chitosan nanoneedles ( Figure 5 ) and micelles exhibit significantly enhanced cellular uptake, higher cytotoxicity against folate-receptor-positive tumor cells. 201 , 202 Loaded with HCPT and MTX-dual drug chitosan NPs that exhibit sustained and prolonged drug release properties, as well as effective cellular internalization and enhanced cytotoxicity. 203 Studies have shown that nitric oxide (NO) is an endogenous gas transmitter can overcome multidrug resistance (MDR) by making nitrification of certain tyrosine residue of P-glycoprotein (Pgp) to inhibit the pumping function.…”
Section: Organic Npsmentioning
confidence: 99%
“…In vitro and In vivo [183] Electrospun fibers-based NPs Chemotherapy In vivo [185,192] Chemotherapy In vitro and In vivo [186][187][188]190] Polysaccharide-based (Chitosan) NPs Chemotherapy In vitro [197,199] Chemotherapy In vitro and In vivo [198,[201][202][203] Chemotherapycombined with Gas Therapy In vitro and In vivo [ In vivo [284] Chemotherapy In vitro and In vivo [281,282,285,286] Chemotherapy combined with PDT In vitro and In vivo [278,279] https://doi.org/10.2147/IJN.S377149…”
Section: Chemotherapymentioning
confidence: 99%
“…In addition, the manufacturing of nanoparticles typically requires the use of organic solvents, which can be difficult to completely remove from the final formulation. 47…”
Section: Liposomes and Nanoparticlesmentioning
confidence: 99%
“…In these NDDSs, various functional molecules were integrated to guide the particles to accumulate at the tumor site ( Wang et al, 2017 ). Various targeting molecules, such as folate ( Wu et al, 2017b ; Hamdy Elshazly et al, 2019 ), methotrexate ( Li et al, 2015 ), and hyaluronic acid ( Misra, 2010 ; Choi et al, 2019 ), were selected to modify the NDDSs. They could bind with the specific receptors on the tumor cells to achieve targeted delivery.…”
Section: Introductionmentioning
confidence: 99%